TSWA 3D : Glasgow - Edinburgh - Derry - Newcastle - Liverpool - Birmingham - London - Bristol - Dartmoor. - Cork, Richard (Bristol : TSW - Television South West and South West Arts, 1987)
Allington, Edward ; Collins, Hannah ; Dunhill, Mark ; Joekes, John ; Norman, Jennie ; Goddard, Judith ; Gormley, Antony ; Haselden, Ron ; Housden, Miranda ; Kivland, Sharon ; Warburton, Holly ; Whiteford, Kate ; Wilson, Richard ; Wyllie, George
TSWA 3D : Edward Allington, St. Martin-in-the-Fields, London ; Hannah Collins, Ikon Gallery, Birmingham ; Mark Dunhill / John Joekes / Jennie Norman, Arnolfini Gallery, Bristol ; Judith Goddard, Bellever Tor and Forest, Dartmoor ; Antony Gormley, City Walls, Derry ; Ron Haselden, Bellever Tor and Forest, Dartmoor ; Miranda Housden, Arnolfini Gallery, Bristol ; Sharon Kivland, Bellever Tor and Forest, Dartmoor ; Holly Warburton, The Oratory, Liverpool ; Kate Whiteford, Calton Hill, Edinburgh ; Richard Wilson, Tyn Bridge, Newcastle ; George Wyllie, Finnieston Crane, Glasgow, May / June 1987
boek
Keywords: Groot-Brittannië; Ierland